First aid guidelines for fragile contexts (conflict, disaster and remote areas): Contextualization & Adaptation (International Journal of First Aid Education)
Topic: In situations of remoteness to medical care, disaster or conflict, first aid provision is important but challenging. Education for learners in such contexts needs to be adapted according to resources available. This paper explores the educational approach and adaptations recommended by the 2020 IFRC First Aid, Resuscitation and Education Guidelines and provides a review of them. As a specialist in fragile and harsh contexts, the ICRC has contributed insight which enables the new guidelines to reflect challenges faced by those providing first aid education in peacetime and in war, and in other situations of adversity. Context: First Aid in armed conflicts, disasters and remote settings Adaptation: Educators need to adjust both the first aid skills and the way of teaching to the realities of those providing first aid. In some instances, safety and security of the first aider and the person requiring help should be prioritized over providing care. In remote settings or places where medical assistance is unlikely to be expedient, or in situations where effective first aid might not be possible, the psychological wellbeing of the first aid provider is also important and educators need to prepare their learners for such occurrences. Within the 2020 International First Aid Guidelines, authors tried to reflect the specific circumstances faced by first aiders in fragile settings, aiming to put the learner at the center and adapt the education to their needs and the realities of the resources available to them. Discussion: First aid educators around the world have to understand that guidelines are provided as an evidence-based guiding document which need to be adapted by the educator to the realities faced by the learner. It is their role to give learners the permission and confidence to act as best they can and provide options for delivering alternative care where resources or circumstances are limiting. Conclusions: The specific circumstances of armed conflict, disasters and remote settings will require the first aid educators and first aiders to adapt the scientific evidence of the first aid guidelines to their realities, and in some instances, place safety and security ahead of first aid provision. To increase the likelihood of successful implementation of evidence-based first aid techniques and practice, first aid education must consider aspects of context that promote and/or hinder implementation in these settings. Important, but not yet explicit enough in the new guidelines, is the permission needed to be given to first aid educators to create an authentic, intelligent and humanitarian approach to first aid learning. The goal is to encourage people to be creative and adapt to harsh realities using available resources without being distracted by theories which they cannot apply.